Safe Corridor to Access Clivus for Endoscopic Trans-Sphenoidal Surgery: A Radiological and Anatomical Study. - Ye Cheng (PLoS ONE, 2015)
Penetration of the clivus is required for surgical access of the brain stem. The endoscopic transclivus approach is a difficult procedure with high risk of injury to important neurovascular structures. We undertook a novel anatomical and radiological investigation to understand the structure of the clivus and neurovascular structures relevant to the extended trans-nasal trans-sphenoid procedure and determine a safe corridor for the penetration of the clivus.We examined the clivus region in the computed tomographic angiography (CTA) images of 220 adults, magnetic resonance (MR) images of 50 adults, and dry skull specimens of 10 adults. Multiplanar reconstruction (MPR) of the CT images was performed, and the anatomical features of the clivus were studied in the coronal, sagittal, and axial planes. The data from the images were used to determine the anatomical parameters of the clivus and neurovascular structures, such as the internal carotid artery and inferior petrosal sinus.The examination of the CTA and MR images of the enrolled subjects revealed that the thickness of the clivus helped determine the depth of the penetration, while the distance from the sagittal midline to the important neurovascular structures determined the width of the penetration. Further, data from the CTA and MR images were consistent with those retrieved from the examination of the cadaveric specimens.Our findings provided certain pointers that may be useful in guiding the surgery such that inadvertent injury to vital structures is avoided and also provided supportive information for the choice of the appropriate endoscopic equipment.